SOCIAL POLARIZATION AND ITS EFFECTS ON PUBLIC INVESTMENTS - Alexandru NEDELEA; Mehmet ÇANAKCI; Ahmet ARSLAN (USV Annals of Economics and Public Administration, 2021)
In democratic countries, at both local and national level, voters expect a fair and effective provision of services for them. Politicians, on the other hand, strive to increase services for pressure and interest groups and politically close citizens instead of democratic components. Bureaucracy grounds generally steers investments by being on the axis and under the influence of political polarization. This situation both causes the public resources to be spent on inefficient areas and prepares the ground for the emergence of economic and social problems due to polarization. Central government having sufficient resources is decisive in this. However, this situation causes the activity of the state to expand enormously. The main purpose of this study is to examine how social polarization has an impact on public investments at local and central levels. In this study, Turkey's public investment with the local administrations 's politic power to be used to express dummy variable is the party and the use of public resources that might influence the polarization was analyzed by Hausman test. The findings strongly demonstrated that polarization has a significant effect on public investment. In addition, according to the other findings of the research, it can be concluded that the negative effects of political polarization on public investments also bring about social polarization and indirectly paves the way for another problem such as injustice in income distribution. In order to prevent polarization, a number of recommendations are given to politicians to leave certain duties of the central government and the authority to use income sources to local administrations to reduce political and social polarization.